Mediation of Autophagic Cell Death by Type 3 Ryanodine Receptor (RyR3) in Adult Hippocampal Neural Stem Cells - Chung, Kyung Min; Jeong, Eun-Ji; Park, Hyunhee; An, Hyun-Kyu; Yu, Seong-Woon (Frontiers in Cellular Neuroscience, 2016)
Cytoplasmic Ca2+ actively engages in diverse intracellular processes from protein synthesis, folding and trafficking to cell survival and death. Dysregulation of intracellular Ca2+ levels is observed in various neuropathological states including Alzheimer’s and Parkinson’s diseases. Ryanodine receptors (RyRs) and IP3 receptors (IP3Rs), the main Ca2+ release channels located in endoplasmic reticulum (ER) membranes, are known to direct various cellular events such as autophagy and apoptosis. Here we investigated the intracellular Ca2+-mediated regulation of survival and death of adult hippocampal neural stem (HCN) cells utilizing an insulin withdrawal model of autophagic cell death. Despite comparable expression levels of RyR and IP3R transcripts in HCN cells at normal state, the expression levels of RyRs — especially RyR3 — were markedly upregulated upon insulin withdrawal. While treatment with the RyR agonist caffeine significantly promoted the autophagic death of insulin-deficient HCN cells, treatment with its inhibitor dantrolene prevented the induction of autophagy following insulin withdrawal. Furthermore, CRISPR/Cas9-mediated knockout of the RyR3 gene abolished autophagic cell death of HCN cells. This study delineates a distinct, RyR3-mediated ER Ca2+ regulation of autophagy and programmed cell death in neural stem cells. Our findings provide novel insights into the critical, yet understudied mechanisms underlying the regulatory function of ER Ca2+ in neural stem cell biology.